Short essay on anthropotechnies and the complexity to define the human being - Daros, W. R. (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This article focuses on describing the problematic about whether humans should remain trapped in a blind biological evolution, or they must move on to choose what they want to assume. Faced with this dilemma, the optimistic hypothesis (achieving a transhumanism) and the pessimistic hypothesis (the degeneration of the human) are remembered. Apparently, the human species, like the rest of the living species, has arisen in a process of evolution; it is the only one with the capacity to be aware of this and, in part, it has been able, by means of techniques, to be able to adapt and to plan part of its future. Biotechnologies are increasingly used for the improvement and perfection of the human, thus becoming anthropotechnics. So, by orienting itself to new technologies towards and over its author, the human being can also become a danger to himself. The «transhumanists» estimate, however, that humans must wrest their biological destiny from the blind process of the evolution of random variation and adaptation and move on to the next stage as a species: the choice of our being. In the conclusion, the implications and consequences of being human and rational are evident.
Keywords: anthropotechnics; human being; adaptation; choice; transhuman